Experimental study on collapse of cracked stiffened plate with initial imperfections under compression. (May 2017) - Shi, Xing Hua; Zhang, Jing; Guedes Soares, C.
Abstract: The collapse mechanics and ultimate strength of crack damaged stiffened plates are investigated by testing stiffened plates with an initial crack. A series of stiffened plates with initial distortions and with a crack are subjected to in-plane compression until achieving their ultimate strength. The crack position, length and the angle between the crack and longitudinal stiffener are changed for determining the influence of the crack on the plate ultimate strength. The ultimate strength and the strain response of the panels are reported. Finally, the ultimate strength reduction related with the presence of the crack and the failure mode are discussed for establishing a damage tolerant procedure for the design of ship structures. Highlights: The collapse mechanics of cracked stiffened plates are investigated by tests. A series of tests were conducted to study the influence of crack damage. The crack and initial deformation reduce the ultimate strength significantly. The crack may play a role in the influence on the stress distribution at crack tip. Some expressions are given for the ultimate strength of cracked stiffened plates.